Sustainable, integrated control of native vectors: The case of Chagas disease in Central America - Dorn, Patricia L.; Monroy, M. Carlota; Stevens, Lori (Frontiers in Tropical Diseases, 2022)
Despite successes in reducing transmission, Chagas disease (American trypanosomiasis) remains the greatest economic burden of any parasitic disease in Latin America afflicting mostly the poor and further contributing to poverty. We review a long-term (2001-2022), integrated Ecohealth approach that addresses sustainable development goals to reduce risk of Chagas transmission by the main native vector in Central America, Triatoma dimidiata, s.l. The basis of the Ecohealth intervention was the identification of the risk factors for house infestation, an understanding of and collaboration with local communities, and genetic and proteomic studies that revealed the epidemiology and mechanisms of the rapid reinfestation seen following insecticide application. We review the development of this approach from a pilot project in two Guatemalan villages, to an expanded initiative across three countries with vastly different ecology, cultures, and municipal organization, and finally development of a multi-institutional, large-scale project to develop a strategy to tackle the remaining hot spots in Central America. This integrated Ecohealth approach resulted in reduced risk of transmission as measured by a sustained decrease in house infestation without further use of insecticides, a reduction in vectors with human blood meals and the Chagas parasite, as well as other health and economic benefits. We discuss lessons learned and how this approach could be applied to other vector-borne diseases.